Implementasi Akad Istishna’ dalam Usaha Konveksi pada DR Konveksi Desa Sragi Kecamatan Songgon - Muh. Khoiruddin; Dimas Alfayit (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to explore the process of buying and selling transactions and the implementation of istishna contracts in DR Konconvection Sragi Village, Songgon District. The method used is qualitative research with the use of various data collection techniques, such as observation, interviews, and documentation. Researchers act as the main instrument in data collection, with data analysis involving collecting, presenting, reducing, and drawing conclusions. The results showed that the implementation of the istishna contract in the DR Convection of Sragi Village, Songgon District allows flexibility and strong cooperation in buying and selling transactions through orders. The process begins with a request from the buyer, who has the freedom to choose the product and determine its specifications. The advance payment shows the seriousness of the buyer and provides start-up capital to start production. The production process focuses heavily on quality, through good communication throughout the process to ensure customer engagement. The implementation of the istishna contract in DR Konconvection of Sragi Village, Songgon District reflects effective collaboration between convection and customers in creating products that suit customer needs and preferences.